Quantum and classical nondeterministic OBDDs - Gainutdinova, A. F. (Učënye zapiski Kazanskogo universiteta. Seriâ Fiziko-matematičeskie nauki, 2024)
A model of nondeterministic ordered binary decision diagrams (NOBDDs) was analyzed. A method for proving a lower bound on the complexity of quantum NOBDDs was developed. Two functions were introduced: one function has linear complexity in the quantum NOBDD but constant complexity in the classical NOBDD, while the other function demonstrates the same complexity in both quantum and classical NOBDD models. The relationships among the complexity classes specific to the OBDD model were described.